"Ethics in governance/ edited by T.K. Mishra, S.P. Aggarwal and Bipin Tiwary" - "Mishra, T.K. (ed.);Aggarwal, S.P. (ed.);Tiwary, Bipin (ed.) " (New Delhi, 2011)
Amidst modern complexities and riddles, executives and organizational heads face immense ethical dilemmas in their decision-making. Circumstantial adversaries pose unique challenge and threat to their conscience and leadership abilities. This book tends to address such dilemmas, threats and challenges in a rather systematic and elucidate manner. It attempts to construct perspectives that may find practical solutions to governance complexities and moral conflicts. This is a book full of people, many of them who took part in a national seminar on 'Ethical dimensions of governance' organized at India International Centre: executives, politicians, jurists, media people, medical practitioners, academicians, and organizational heads. Those who were philosophically as well as emotionally interested in the inter-faith debate and who believed in creating a synthesis of different belief systems on governance. So there is a kind of moral dialogue and deliberations that are captured by the authors. There are countless anecdotes, some humorous and some poignant, and they are fascinating also because such people have never been so exuberant in the public eye anyway.
Keywords: Political ethics